2022
DOI: 10.3390/antiox11050938
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Faba Bean Hull Nanoparticles on Physical Properties, Protein and Lipid Oxidation, Colour Degradation, and Microbiological Stability of Burgers under Refrigerated Storage

Abstract: The processing of faba beans generates great quantities of hulls, which are high in bioactive compounds with demonstrated radical-inhibiting properties. There is no research on the impact of using faba bean hull nanoparticles (FBH-NPs) to improve the quality and extend the shelf-life of beef products. Hence, the target of this investigation was to assess the inhibiting influence of adding FBH-NPs at two different concentrations (1 and 1.5%) on the physical attributes, lipid and protein oxidation, colour degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Due to the high TPC, husks of faba beans have high antioxidant properties. In experiments with enriched burger patties, results showed that faba bean husks improved cooking properties, delayed lipid and protein oxidation, prevented colour changes, and decreased the microbiological load of burger patties [147].…”
Section: Husks-food Usementioning
confidence: 99%
“…Due to the high TPC, husks of faba beans have high antioxidant properties. In experiments with enriched burger patties, results showed that faba bean husks improved cooking properties, delayed lipid and protein oxidation, prevented colour changes, and decreased the microbiological load of burger patties [147].…”
Section: Husks-food Usementioning
confidence: 99%
“…Faba bean, also known as fava bean or broad bean (Vicia faba L., Fam. Fabaceae), is an economically important legume crop worldwide (Elsebaie et al, 2022). It is among the healthiest staple foods in the Egyptian diet that provide the majority of necessary macronutrients (such as proteins, fiber, and carbohydrates) and main vitamins and minerals (El-Metwally et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…needs, so Egypt resorts to importing seeds of faba bean from other countries mostly from Australia, France and the United Kingdom (Attia et al, 2019). To date, Egypt remains the biggest importer of faba bean crop in the world as it imports more than 50% of the total import volume in the world (Attia et al, 2019;Elsebaie et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Faba bean, Vicia faba L. (Family: Fabaceae) is one of the oldest economic legume crops globally (Elsebaie et al 2022) which is believed to be originated in the Near East (Merga et al 2019). Worldwide, the most producing countries of this crop are China, Ethiopia, France, Egypt, and Australia (Abdelhaleim et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Under global warming and climatic change, V. faba is probably one of the bestperforming crops as its better ability to grow under all different climatic conditions as well as its high adaptability to a variety of soil environments (Singh et al 2013). Unfortunately, Egypt has ranked as the top importer of this vital crop in the world till now, importing more than 50% out of the total import volume every year (Elsebaie et al 2022) from other producer countries such as Australia, France and the United Kingdom. In spite of Egypt's self-su ciency of this crop was determined to be 115% in the 1970s, then this percentage dramatically decreased since the 1980s, until registering 26.9% in 2020 (FAOSTAT 2020).…”
Section: Introductionmentioning
confidence: 99%